What Drives Demand for Private Tutoring in the Middle East and North Africa Region? Evidence from a Youth Survey - Ali Fakih; Nathir Haimoun; Anastasia Sleiman (Institute of Labor Economics (IZA), 2022)
This paper examines the determinants of private tutoring in five major Middle East and North Africa (MENA) countries, Egypt, Algeria, Lebanon, Morocco, and Tunisia. The paper uses data extracted from the SAHWA Youth Survey (2016) and runs a probit model. The main findings indicate that age, receiving financial support, having educated parents, and living in urban areas increase the demand for private tutoring. Conversely, the results show that being a male student or a child of an employed mother would decrease the need for a private tutor. The empirical findings propose potential policy implications for MENA countries facing exacerbating gaps in the education system while emphasizing the challenges hindering public schools from delivering quality education.
Keywords: I21; I22; I24; 330; private tutoring; shadow education; youth; MENA region; probit model